IoT in Agriculture: Ongoing Developments and Emerging Issues (International Journal of Innovative Research in Computer Science & Technology, 2020)
The developing requirement for food, both  as far as amount and quality, has required horticultural area  improvement and industrialization. The "Web of Things"  (IoT) is a promising group of innovations fit for giving an  assortment of answers for farming modernization. Logical  associations and exploration establishments, as well as the  horticultural area, are hustling to give increasingly more  IoT answers for rural business partners and to set the  foundation for a characterized job when IoT turns into a  standard innovation. Simultaneously, Cloud Computing  and Fog Computing, the two of which are presently very  well known, offer satisfactory assets and advances to keep  up with, store, and break down the gigantic amounts of  information created by IoT gadgets. The organization and  examination of IoT information might be utilized to  computerize tasks, expect occasions, and improve an  assortment of exercises progressively. Besides, the  possibility of interoperability across heterogeneous  gadgets prodded the advancement of appropriate  apparatuses that might be utilized to fabricate new  applications and administrations that increase the value of  information streams produced at the organization's edge.  Remote Sensor Network (WSN) advances fundamentally  affect farming, and the Internet of Things is expected to  have a comparable effect. An audit of contemporary IoT  advances is given in this article, alongside their current  infiltration in the rural area, their possible worth for future  ranchers, and the challenges that IoT goes up against in its  spread.
Keywords: Cloud; Food supply chain; Internet of things; RFID; Wireless sensor networks